Efficacy and Safety of a Subanesthetic Dose of Esketamine Combined with Propofol in Patients with Obesity Undergoing Painless Gastroscopy: A Prospective, Double-Blind, Randomized Controlled Trial - Zheng L; Wang Y; Ma Q; Liang W; Zhang X; Ren Z; Qin W; Meng F; Li Y; Fan G; Yin N (Dove Medical Press, 2023)
Longbin Zheng,1,* Yiteng Wang,2,* Qing Ma,1,* Wenbo Liang,1 Xiaojing Zhang,1 Zhiqiang Ren,1 Weimin Qin,1 Fan Meng,1 Yuhong Li,1 Guoxiang Fan,1 Ning Yin1 1Department of Anesthesiology, Sir Run Run Hospital, Nanjing Medical University, Nanjing, Jiangsu Province, People's Republic of China; 2Department of Anesthesiology, Xinchang County People's Hospital, Xinchang, Zhejiang Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Ning Yin, Department of Anesthesiology, Sir Run Run Hospital, Nanjing Medical University, No. 109 Longmian Avenue, Nanjing, Jiangsu Province, 211112, People's Republic of China, Email yinning882000@126.comPurpose: Patients with obesity are more susceptible to hypoxemia. Anesthetic management for patients with obesity undergoing painless gastroscopy presents a severe challenge for anesthesiologists. Esketamine is a NMDA antagonist that has been proven to be beneficial for ameliorating respiratory depression owing to its sympathomimetic effect; however, there are no relevant reports on its use in patients with obesity. We designed a randomized controlled trial to evaluate whether esketamine can be the ideal adjuvant to propofol sedation in patients with obesity undergoing painless gastroscopy.Patients and Methods: A total of 104 patients with obesity undergoing painless gastroscopy were randomly divided into group C (propofol+saline) and group S (propofol+esketamine 0.25 mg/kg). Anesthesia was induced by 2 mg/kg propofol with saline or esketamine. The consumption of propofol, hemodynamic parameters, duration of procedure, induction time, postoperative awakening time, and orientation recovery time were recorded. Adverse events and satisfaction scores were also recorded.Results: Propofol consumption was 274.4± 22.6 mg and 201.3± 16.6 mg in groups C and S, respectively. The induction time of groups C and S were 25.4± 2.3 s and 17.8± 1.9 s, respectively. The postoperative awakening times of groups C and S were 6.2± 1.1 min and 4.8± 1.3 min, respectively. Hemodynamic parameters were more stable in group S than in group C. The incidence of adverse events such as injection pain, hypoxemia, hypotension, bradycardia, choking, and body movement were significantly lower in group S. The satisfaction scores of the endoscopist and anesthesiologist were (4.58± 0.49 vs 3.71± 0.83) and (4.75± 0.44 vs 3.33± 0.92), respectively.Conclusion: The combination of propofol and esketamine (0.25 mg/kg) improves the safety and reduces the incidence of adverse events in patients with obesity during painless gastroscopy. Thus, this method is worthy of clinical application.Clinical Trials Registration: ChiCTR 2200062547.Keywords: esketamine, propofol, patients with obesity, painless gastroscopy